Freedom of Speech in Universities Islam, Charities and Counter-terrorism - Scott-Baumann, Alison (Islam in the World, 2021)
Freedom of speech and extremism in university campuses are major sources of debate and moral panic in the United Kingdom today. In 2018, the Joint Committee on Human Rights in Parliament undertook an inquiry into freedom of speech on campus. It found that much of the public concern is exaggerated, but identified a number of factors that require attention, including the impact of government counter-terrorism measures (the Prevent Duty) and regulatory bodies (including the Charity Commission for England and Wales) on freedom of speech. This book combines empirical research and philosophical analysis to explore these issues, with a particular focus on the impact upon Muslim students and staff. It offers a new conceptual paradigm for thinking about freedom of speech, based on deliberative democracy, and practical suggestions for universities in handling it. Topics covered include: The enduring legacy of key thinkers who have shaped the debate about freedom of speech The role of right-wing populism in driving moral panic about universities The impact of the Prevent Duty and the Charity Commission upon Muslim students, students' unions and university managers Students' and staff views about freedom of speech Alternative approaches to handling freedom of speech on campus, including the Community of Inquiry This highly engaging and topical text will be of interest to those working within public policy, religion and education or religion and politics and Islamic Studies.